Introduction to special issue: stranded assets and the environment - Caldecott, B (Taylor and Francis, 2016)
Since 2011 the topic of ‘stranded assets’ created by environment-related risk factors, including physical climate change impacts and societal responses to climate change, has risen up the agenda dramatically. The concept has been endorsed by a range of significant international figures. The emergence of the topic should be of significant interest to scholars and practitioners alike, as it has influenced many pressing topics facing investors, companies, policy-makers, regulators, and civil society in relation to global environmental change.